Design of a joint research data platform: A use case for severity assessment. (February 2020) - Talbot, Steven R; Bruch, Stefan; Kießling, Fabian; Marschollek, Michael; Jandric, Branko; Tolba, René H; Bleich, André
Severity assessment in animal models is a data-driven process. We therefore present a use case for building a repository for interlaboratory collaboration with the potential of uploading specific content, making group announcements and internal prepublication discussions. We clearly show that it is possible to offer such a structure with minimal effort and a basic understanding of web-based services, also taking into account the human factor in individual data collection. The FOR2591 Online Repository serves as a blueprint for other groups, so that one day not only will data sharing among consortium members be improved but the transition from the private to the persistent domain will also be easier.